Evaluation of the Antioxidant Activity of Ficus Racemosa Plant Extracts From North-Western District of Bangladesh - Sultana, Johora; Kabir, AS; Hakim, Md Abdul; Abdullah, M; Islam, N; Reza, Md Abu (Journal of Life and Earth Science, 2014)
Antioxidant is a new hype in naturopathy and at present it has huge demand in cosmetic, nutritional supplementation and pharmacological industry. It reduces cell damages caused by free-radical which are responsible for various ailment like ageing, cancer, coronary heart disease, diabetes mellitus, neurodegenerative disorders, atherosclerosis, cataracts and inflammation. At present any comprehensive data on the antioxidant content and extent of their activity of the indigenous medicinal plants of Bangladesh is not available. Therefore, here antioxidant activity of a popular medicinal plant - Ficus racemosa was determined. Methanolic extract was prepared from the leaf and stem bark of F. racemosa. Their total phenolics and free radical scavenging capacity was determined using folin-ciocalteu reagent (FCR) assay and DPPD-radical scavenging assay respectively. Stem bark and leaves of F. racemosa contains 242.97 and 235.45 mg of GAE / gm of dried extract of phenolics respectively. Current studies also show that F. racemosa barks contain a high antioxidant activity. IC50 value of bark extract was found to be 19?g/ml which is even better that of the standard BHT. Therefore, present studies suggest that F. racemosa bark has a huge potential in terms of commercial use as source of antioxidant. DOI: http://dx.doi.org/10.3329/jles.v8i0.20152 J. Life Earth Sci., Vol. 8: 93-99, 2013